2021
DOI: 10.1109/tcst.2020.2969124
|View full text |Cite
|
Sign up to set email alerts
|

Robust Attitude Tracking for Aerobatic Helicopters: A Geometric Approach

Abstract: This paper highlights the significance of the rotor dynamics in control design for small-scale aerobatic helicopters, and proposes two singularity free robust attitude tracking controllers based on the available states for feedback. 1. The first, employs the angular velocity and the flap angle states (a variable that is not easy to measure) and uses a backstepping technique to design a robust compensator (BRC) to actively suppress the disturbance induced tracking error. 2. The second exploits the inherent damp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The linearized equation is given by i=1ê i PR eqêi , and I I I is the 3 × 3 identity matrix. Details of the linearization procedure are given in [24]. For positive values of the gains k R , k ω , ζ i , Ω i it is observed that S(R eq ) is hyperbolic for all R eq ∈ Θ.…”
Section: Attitude Tracking Controllermentioning
confidence: 99%
See 4 more Smart Citations
“…The linearized equation is given by i=1ê i PR eqêi , and I I I is the 3 × 3 identity matrix. Details of the linearization procedure are given in [24]. For positive values of the gains k R , k ω , ζ i , Ω i it is observed that S(R eq ) is hyperbolic for all R eq ∈ Θ.…”
Section: Attitude Tracking Controllermentioning
confidence: 99%
“…The gain matrices K X , K Y and D X , D Y are composed of natural frequency and damping parameters as in (24).…”
Section: Controller Structurementioning
confidence: 99%
See 3 more Smart Citations